Daily activity and functional performance in people with chronic disease: A cross-sectional study - Erhard Næss-Schmidt; Asger Pedersen; David Christiansen; Nils-bo Andersen; John Brincks; Bernd Grimm; Jørgen Nielsen; Inger Mechlenburg (Cogent Medicine, 2020)
The aim of this study was to describe the physical activity profiles, in patients with stroke, Parkinson’s disease, multiple sclerosis and rheumatoid arthritis and to investigate the association between physical activity and functional performance. Physical activity profiles were conducted using tri-axial accelerometers and functional performance was examined by the “Six-Spot Step Test” and the “Timed Up and Go”. Patients daily performed 5896 ± 3176 steps with an average cadence of 88.3 ± 11.1, 368 ± 418 inclined walking steps and 50 ± 16 sit-stand transfers. Daily activity was modestly explained by functional performance. The activity profiles showed a large variance in activity parameters and results suggest that activity parameters and the two functional performance tests are different constructs.